Antecedents of use of e-health services in Central Eastern Europe: a qualitative comparative analysis - Marek Ćwiklicki; Francesco Schiavone; Jacek Klich; Kamila Pilch (BMC, 2020)
Abstract Background The objective of this paper is to identify the key conditions that positively affect the use of e-health services in Central Eastern Europe (CEE) countries. CEE countries after the political and economic transformation in 1989/90 implemented slightly different national health care models. The research question of the study is: how do the various institutional conditions at the national level affect the use of e-health services in CEE countries? Methods The e-health description was derived from papers indexed in Web of Science and Scopus. The data for computation were collected from the 2015 global survey by the WHO Global Observatory for eHealth. We used a narrative literature review in order to identify key terms associated to e-health and conditions for the implementation of e-health services. The search terms were "e-health" and "*" where * was particular thematic section of e-health according to WHO GOeH. The inclusion criterion was relevance of the paper to e-health and searched phase. Eligibility criteria for countries for being described as CEE countries: Estonia, Lithuania, Latvia, Poland, Hungary, Romania, Bulgaria, Czech Republic, Slovenia, and Croatia (we omitted Slovakia from the analysis because this country was not covered by the WHO Survey). We applied qualitative comparative analysis (QCA) to analyse the necessary order of conditions. The dependent variable of the study is the national rate of use of e-health services. Results QCA shows that legal medical jurisdiction, teleprogramme and electronic health records supplemented by adequate training constitute critical conditions to achieve success in e-health implementation. Conclusions We conclude that the more formalised a framework for e-health service delivery is, the more likely it will be used. Therefore formalisation fosters the diffusion, dissemination and implementation of e-health solutions in this area. Formalisation must be accompanied by tailored training for health care professionals and patients. Our analyses are related only to the paths of e-health implementation in CEE countries thus consequently the findings and conclusions cannot be directly applied to other countries. The limitations of this study are related the absence of a broader context of e-health development, including the development of ICT infrastructure and ICT literacy.